Alkynyl-modified acylhydrazone covalent organic framework material, preparation method and application of alkynyl-modified acylhydrazone covalent organic framework material in fuel cell

By self-assembly forming alkynyl-modified acyl-hydrazone covalent organic frame material under solvothermal conditions, the shortcomings in existing materials in terms of mechanical properties and chemical tunability are solved, and the proton conduction and mechanical properties are improved in fuel cells.

CN119684548AActive Publication Date: 2025-03-25CHINA THREE GORGES UNIV

Patent Information

Application Number
CN202411636089.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing covalent organic frame materials have shortcomings in mechanical properties and chemical tunability, which are prone to fracture and difficult to undergo high selectivity chemical modification, which limits their application in fuel cells and other fields.

Method used

The porosity and mechanical properties of the material are improved and its chemical tunability are enhanced by self-assemblying the alkynyl-modified acyl-modified organic framework material under solvothermal conditions.

Benefits of technology

This material exhibits excellent performance in proton conduction and mechanical properties, has better elasticity and plasticity, and through the active functional groups of alkynyl groups, new functional groups can be further introduced to improve the conductivity of the proton exchange membrane in fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684548A_ABST
    Figure CN119684548A_ABST
Patent Text Reader

Abstract

The invention relates to an alkynyl-modified acyl covalent organic framework (COF) material and application thereof, and relates to the field of preparation of crystalline porous materials and fuel cells. The material is a covalent organic framework material which is synthesized by taking 1, 3, 5-triformyl phloroglucinol and 2, 5-bis (2-propynyloxy) terephthaloyl hydrazine as raw materials through solvothermal reaction under specific conditions, and has relatively high crystallinity. The material has good performance in the aspect of proton conductivity, the highest proton conductivity can reach 6.16163 * 10 <-4 > S / cm, and the mechanical property is enhanced due to introduction of alkynyl. Alkynyl is used as an active functional group, and various chemical reactions can be derived, so that the potential application value of the material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an alkyne-modified acylhydrazone covalent organic framework material. The material has excellent mechanical properties and chemical adjustability and is applicable to fuel cell technology. Background Art

[0002] In recent years, as one of the key components in electrochemical devices, the proton exchange membrane of the fuel cell plays the role of isolating the anode and cathode inside the battery, and is responsible for the conduction of protons and participates in the charge balance process in the electrochemical reaction. Therefore, the performance and quality of the battery proton exchange membrane have an important impact on the output power, efficiency, life and stability of the battery. At present, various materials, such as various MOFs and various porous organic polymers, have been widely used in fuel cells.

[0003] Covalent Organic Frameworks (COFs) are a new type of crystalline porous materials. They are ordered porous network structures formed by organic monomers through covalent bonds. Due to their high porosity, large specific surface area, adjustable pore size and porosity, COFs have good application prospects in optoelectronic fields such as photocatalysis, proton conduction, gas storage, and energy storage.

[0004] The current COF material structure is prone to breakage when subjected to external forces due to its highly ordered pore structure and rigid covalent bond connection, lacking sufficient toughness and elasticity; and under certain conditions, the mechanical stability of COF materials may decrease, resulting in structural damage or performance degradation; in addition, COF materials prepared in the laboratory are usually powdered, and processing them into films or other forms may reduce their mechanical strength, limiting their application in some fields. Not only that, in terms of chemical adjustability, although the synthesis path of COF allows a certain degree of pre-design and functionalization, it is still difficult to introduce new functional groups or further modify existing functional groups after material synthesis. Therefore, for chemical modifications that require high selectivity, the existing COFs system may be difficult to meet the requirements. The present invention uses a cheap and readily available monomer 1,3,5-triformyl phloroglucinol and 2,5-bis (2-propynyloxy) terephthaloyl hydrazide to self-assemble under solvent thermal conditions to form an acetyl modified hydrazone COF material. The COF crystal structure has a high porosity, and the introduction of alkynyl groups reduces the overall rigidity of the material, making COF more elastic and plastic. In addition, the alkynyl group is an active functional group that can be further derivatized through various reactions. This modifiability can be used to introduce new functional groups, thereby changing the physical and chemical properties of the material. Summary of the invention

[0005] The present invention relates to a preparation method of an acylhydrazone covalent organic framework material modified by an alkynyl group and its application in fuel cells. The material uses 1,3,5-triformylphloroglucinol and 2,5-bis(2-propynyloxy)terephthaloylhydrazide as raw materials, and obtains a covalent organic framework material with high crystallinity through a reaction under solvent thermal conditions. The material exhibits good performance in proton conduction. In addition, since the material structure contains an alkynyl group, the presence of the alkynyl group enhances the mechanical properties of the material to a certain extent. As an active functional group, the alkynyl group can be further derivatized through various reactions, introducing new functional groups, changing the physical and chemical properties of the material, and thus improving the conductivity of the proton exchange membrane in the fuel cell.

[0006] An object of the present invention is to provide an acetylhydrazone covalent organic framework material modified by an alkynyl group, the structural formula of which is as follows:

[0007]

[0008] There is an alkoxyalkynyl side chain in the structural formula of the film material; there is an acylhydrazone bond -C=O(NH-NH2) in the structure of the film material.

[0009] The organic framework material includes characteristic diffraction peaks at about 3°, 7° and 27° 2θ angles. The organic framework material includes a diffraction peak at about 3305 cm -1 、2125cm -1 and 1643cm -1 A characteristic infrared absorption peak appears at this position.

[0010] The preparation method of the alkyne-modified acylhydrazone covalent organic framework material comprises the following steps:

[0011] Mix 2,5-bis(2-propynyloxy)terephthaloylhydrazide and 1,3,5-triformylphloroglucinol in a reaction bottle, add an organic solvent, and after ultrasonic treatment and uniform dispersion, add an acid solution as a catalyst;

[0012] Then, it is quickly frozen, vacuumized, and heated in an oil bath after the bottle mouth is sealed; after the oil bath reaction is completed, the solid product is washed with a solvent, and after a certain period of extraction, it is filtered and dried to obtain an acylhydrazone covalent organic framework material modified by an alkyne group. The specific reaction formula is as follows:

[0013]

[0014] The molar ratio of 2,5-bis(2-propynyloxy)terephthaloyl hydrazide to 1,3,5-triformyl phloroglucinol is 1-3:1-3; preferably, the ratio of 2,5-bis(2-propynyloxy)terephthaloyl hydrazide to 1,3,5-triformyl phloroglucinol is 2-2.5:1.5-2.0.

[0015] The organic solvent is a combination of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, mesitylene, 1,4-dioxane, o-dihydrobenzene, n-butanol and benzyl alcohol; the preferred solvent is mesitylene, 1,4-dioxane and n-butanol.

[0016] In some embodiments, the organic solvent is a mixed solvent and is mixed in a certain ratio of 1-3:1-4; the preferred solvent ratio is 4-5:1-2 for mesitylene and 1,4-dioxane.

[0017] The acid solution is an acetic acid aqueous solution or a hydrochloric acid aqueous solution; the concentration of the acid solution is 3M-12M; the concentration of the acid solution is preferably 3-6M.

[0018] The reaction temperature range of the heating in the oil bath pot is 100-150°C; the reaction temperature is preferably 100-120°C; the reaction time of the heating in the oil bath pot is 12-144h; the reaction time is preferably 36-48h.

[0019] In some embodiments, the solvent used when washing the solid product with a solvent is one of acetone, ethyl acetate, dichloromethane, methanol, ethanol, 1,4-dioxane, N,N-dimethylformamide, tetrahydrofuran, ammonia water and deionized water; the solvent used for washing is preferably acetone, 1,4-dioxane, tetrahydrofuran, deionized water or ethanol.

[0020] The type of solvent selected during the extraction is one of acetone, ethyl acetate, dichloromethane, methanol, ethanol, 1,4-dioxane and tetrahydrofuran; the solvent selected during the extraction is preferably tetrahydrofuran and acetone; the extraction time is 12-72h; the extraction time is preferably 48h.

[0021] A proton conductor for a fuel cell comprises the alkyne-modified acylhydrazone covalent organic framework material or the alkyne-modified acylhydrazone covalent organic framework material prepared by the method.

[0022] The obtained sample was activated by soaking in methanol for a period of time, and then dried at a certain temperature, collected and ground, and then pressed and pressed into tablets after being vibrated. The samples were fixed with 5-50μm gold wires, and conductive silver paste was applied on both sides. After the samples were dried, they were placed in a constant humidity and temperature environment, and the EIS impedance analyzer was used to test and fit the corresponding fitting internal resistance of the samples at the humidity and temperature. Then, different temperatures and humidities were adjusted, and the EIS impedance analyzer was used to test and fit the fitting internal resistance of the samples at different humidity and temperature, and the conductivity and activation energy were calculated.

[0023] The tabletting pressure is 100-400 kg / cm 2 The tableting time is 0.5-5min, the thickness is 0.50-3.50mm; preferably 250kg / cm 2 The tableting holding time is 0.5-5 min, preferably 1 min, and the thickness is 0.50-3.50 mm, preferably 3 mm.

[0024] In the step, after the conductive silver paste is applied, the drying temperature is 30-70° C., preferably 50° C., the drying time is 10-50 min, preferably 15 min, and the fixed humidity is 90-98%.

[0025] During the stability performance test, the sample obtained in the test is placed in a closed environment. The humidity is set at 90-98% by program setting, and the temperature is first increased from 30°C to 90°C, and then decreased from 90°C to 30°C. After a plurality of continuous temperature rise and fall cycles, the operation (3) is repeated again to analyze whether the proton conductivity changes. In the stability test, the humidity is 50-98%, the temperature before the increase is 20-35°C, and the temperature after the increase is 85-95°C, and the number of cycles is greater than or equal to 2 times.

[0026] The specific beneficial effects of this material are as follows:

[0027] 1. Cost-effectiveness and structural advantages: 1,3,5-triformylphloroglucinol, as an organic monomer, provides an economical and efficient solution for material synthesis with its simple structure and relatively low price;

[0028] 2. Enhanced ion conductivity: Its hydroxyl coordination mode is rich, which not only forms a stable coordination with the main material, but also significantly improves the conductivity of hydrogen ions and optimizes the ion conductivity of the material;

[0029] 3. Excellent stability: The CTGU-COF material can remain stable in harsh environments such as acid, alkali and boiling water, demonstrating its excellent weather resistance and durability;

[0030] 4. Improved processing performance: The introduction of alkynyl groups reduces the rigidity of the material, giving it good elasticity and plasticity, making it easier to process and shape, and broadening its application range;

[0031] 5. Flexible functionalization capability: Alkyne, as an active functional group, can easily introduce new functional groups through chemical reactions, providing unlimited possibilities for regulating the physical and chemical properties of materials;

[0032] 6. Potential optical properties: The unique optical properties that may be brought about by the participation of alkyne groups in the conjugated system indicate the great potential of this material in the field of optoelectronic devices and sensors; BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the structural formula diagram of CTGU-COF prepared in Example 1 of the present invention.

[0034] Figure 2 This is the IR graph of CTGU-COF prepared in Example 1 of the present invention.

[0035] Figure 3 The XRD diagram of the CTGU-COF prepared in Example 1 of the present invention and its XRD diagram immersed in different acid and alkali media.

[0036] Figure 4 2,5-bis(2-propynyloxy)terephthaloylhydrazide in the present invention 1 H NMR spectrum.

[0037] Figure 5 2,5-bis(2-propynyloxy)terephthaloylhydrazide in the present invention 13 C NMR spectrum.

[0038] Figure 6 This is the EIS diagram of the CTGU-COF material in the present invention.

[0039] Figure 7 This is the conductivity diagram of the CTGU-COF material in the present invention.

[0040] Figure 8 It is the Arrhenius plot of the CTGU-COF material in the present invention. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0042] Example 1

[0043] 2,5-bis(2-propynyloxy)terephthaloylhydrazide (69.0 mg, 2.2 mmol) and 1,3,5-triformylphloroglucinol (31.5 mg, 1.5 mmol) were added to the ampoule, followed by 1.8 mL of anhydrous 1,4-dioxane and 7.2 mL of mesitylene. After ultrasonication for 30 min, 0.9 mL of acetic acid aqueous solution (6 mol·L -1 ); quickly freeze the ampoule in liquid nitrogen, evacuate the ampoule after complete freezing, and seal the ampoule with a flame spray gun; place the ampoule containing the reactants in an oil bath and heat at 120° C. for 72 h; finally, wash the obtained red-brown solid with DMF and THF in turn, dry and filter it under vacuum at 100° C. to obtain dry CTGU-COF powder.

[0044] Figure 1The structure in FIG. 1 shows that the CTGU-COF mainly undergoes ammonia condensation with the aldehyde group through the hydrazide bond to form an acylhydrazone type organic covalent bond. The figure shows the basic building unit of the CTGU-COF.

[0045] Figure 2 The IR graph in the figure shows that C≡C, C=O, C=O(NH) and the like of the raw material 2,5-bis(2-propynyloxy)terephthaloylhydrazide all appear in the COF; and the primary amine peak in the raw material 2,5-bis(2-propynyloxy)terephthaloylhydrazide disappears, and a new C=N bond appears in the COF, indicating that the COF is successfully prepared.

[0046] Figure 3 The XRD diagram of CTGU-COF in the present invention and its XRD diagrams immersed in different acid and alkali media. After being immersed in boiling water, 12M NaOH, and 12M HCl solution for 12 hours, the structure of COF did not change.

[0047] Figure 4 2,5-Bis(2-propynyloxy)terephthaloylhydrazide 1 The HNMR spectrum shows that the chemical shifts of various H species in 2,5-bis(2-propynyloxy)terephthaloylhydrazide further confirm the structural accuracy of the raw materials; 1 H NMR (500MHz, DMSO-d6) δ9.34(d,J=3.7Hz,2H),7.49(s,2H),4.91(d,J=2.4Hz,4H),4.59(d,J=3.9Hz,4H),3.65(t,J=2.4Hz,2H).

[0048] Figure 5 2,5-Bis(2-propynyloxy)terephthaloylhydrazide 13 The C NMR spectrum shows the chemical shifts of various Cs in 2,5-bis(2-propynyloxy)terephthaloylhydrazide, which further confirms the structural accuracy of the raw material.

[0049] 13 C NMR (126MHz, DMSO-d6) δ163.9,149.2,126.0,115.8,79.5,79.3,57.2.

[0050] The above results show that the alkyne-modified acylhydrazone CTGU-COF material has been successfully synthesized. Its unique alkyne structure gives the material superior mechanical properties and improves chemical adjustability, providing a useful idea for improving the proton conductivity of similar CTGU-COF materials in the future and promoting the application of such materials in the field of hydrocarbon functional groups and electrochemistry.

[0051] Example 1-1

[0052] The other operating steps are the same as those in Example 1, except that the volume ratio of anhydrous 1,4-dioxane to mesitylene is 1:3, the amount of anhydrous 1,4-dioxane is 0.6 mL, and the volume of mesitylene is 1.8 mL. CTGU-COF with good crystallinity can also be successfully prepared.

[0053] Example 1-2

[0054] The other operation steps are the same as those in Example 1. The ampoule containing the reactants is placed in an oil bath and heated at 130° C. for 48 h. CTGU-COF with good crystallinity can also be successfully prepared.

[0055] Examples 1-3

[0056] The other steps were the same as those in Example 1, and then 0.5 mL of acetic acid aqueous solution (12 mol·L -1 ), and CTGU-COF with good crystallinity can also be successfully prepared.

[0057] Example 2

[0058] The test steps for COF proton conductivity are as follows:

[0059] First, the sample was activated with methanol for 3 days. After activation, the sample was placed in a vacuum drying oven at 80°C for 12 hours and then collected. The preparation process of the sheet sample for impedance testing is as follows: First, grind the sample in a mortar for 2 minutes. After grinding, add an appropriate amount of powder sample to the tablet press, shake it evenly, and pressurize it to 250kg / cm 2 , and maintain the pressure for 60s; then, take out the sheet sample and measure its diameter and thickness, and the diameter is 4.00mm and the thickness is 3.00mm; finally, fix the sheet sample with a gold wire with a diameter of 50μm, and apply conductive silver paste on both sides of the sheet sample, and dry it at 50℃ for 15min. Then set the program of the constant temperature and humidity instrument, and adjust the program to set the humidity to 98% and the temperature to 30℃. In order to make the sample to be tested adapt to the humidity and temperature conditions required for the test, it is necessary to first place the sample in the humidity and temperature environment required for the test for 24h before the test, and then use the EIS impedance analyzer to test and fit the corresponding fitting internal resistance of CTGU-COF at different temperatures at 98%RH, and calculate the conductivity and activation energy.

[0060] Figure 6 The EIS of the CTGU-COF material shows that under 98RH%, the resistance value of the CTGU-COF material decreases with increasing temperature, indicating that its conductive performance continues to improve.

[0061] Figure 7The conductivity diagram of the CTGU-COF material shows that the CTGU-COF material has good proton conductivity, and the highest proton conductivity can reach 6.16163×10 -4 S / cm, and its conductivity gradually increases with increasing temperature.

[0062] Figure 8 The Arrhenius plot of the CTGU-COF material shows that the CTGU-COF material transports H + The required activation energy is less than 0.4 eV, which belongs to the proton hopping mechanism and is consistent with the design idea of ​​constructing a hydrogen bond network through the skeleton.

[0063] Example 2-1

[0064] The proton conductivity of COF was tested in the same steps as in Example 2:

[0065] Add an appropriate amount of powder sample to the tablet press, shake it evenly and press it to 350kg / cm 2 , and maintain the pressure for 30s; then, the sheet sample was taken out and its diameter and thickness were measured. The diameter was measured to be 4.00mm, and its thickness still met the proton conduction performance test requirements; and the performance remained stable.

[0066] Example 2-2

[0067] The proton conductivity test of COF was carried out in the same manner as in Example 2, where conductive silver paste was applied to both sides of the sheet sample and dried at 40° C. for 35 min. The sample still met the proton conductivity test requirements and the performance remained stable.

[0068] Example 3

[0069] The cycle stability performance test of COF is as follows:

[0070] The humidity was set at 98% RH through program setting, and the temperature was first increased from 30°C to 90°C, and then decreased from 90°C to 30°C. After two consecutive temperature rise and fall cycles, the test results showed that the proton conductivity of the material did not change significantly, proving the excellent cycle stability of the material.

[0071] The above contents are only preferred embodiments of the present invention and do not limit the scope of the present invention. Therefore, any equivalent or modified contents that do not depart from the spirit disclosed by the present invention belong to the protection scope of the present invention.

Claims

1. An alkyne-modified acylhydrazone covalent organic framework material, characterized in that: The structural formula is as follows:

2. The alkynyl-modified acylhydrazone covalent organic framework material according to claim 1, characterized in that: The organic framework material includes characteristic diffraction peaks appearing near 2θ angles of about 3°, 7° and 27°.

3. The alkynyl-modified acylhydrazone covalent organic framework material according to claim 1, characterized in that: The organic framework material includes about 3305 cm -1 、2125cm -1 and 1643cm -1 A characteristic infrared absorption peak appears at this position.

4. The method for preparing the alkynyl-modified acylhydrazone covalent organic framework material according to any one of claims 1 to 3, characterized in that: The steps include: Mix 2,5-bis(2-propynyloxy)terephthaloylhydrazide and 1,3,5-triformylphloroglucinol in a reaction bottle, add an organic solvent, and after ultrasonic treatment and uniform dispersion, add an acid solution as a catalyst; Then the product is rapidly frozen, vacuumized, and heated in an oil bath after the bottle mouth is sealed; after the oil bath reaction is completed, the obtained solid product is washed with a solvent, and after extraction for a certain period of time, filtered and dried to obtain an acetylhydrazone covalent organic framework material modified with an alkyne group.

5. The method for preparing the alkyne-modified acylhydrazone covalent organic framework material according to claim 4, characterized in that: The molar ratio of 2,5-bis(2-propynyloxy)terephthaloyl hydrazide to 1,3,5-triformyl phloroglucinol is 1-3:1-3; preferably, the ratio of 2,5-bis(2-propynyloxy)terephthaloyl hydrazide to 1,3,5-triformyl phloroglucinol is 2-2.5:1.5-2.

0.

6. The method for preparing the alkyne-modified acylhydrazone covalent organic framework material according to claim 4, characterized in that: The organic solvent is a combination of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, mesitylene, 1,4-dioxane, o-dihydrobenzene, n-butanol and benzyl alcohol.

7. The method for preparing the alkyne-modified acylhydrazone covalent organic framework material according to claim 4, characterized in that: The acid solution is an acetic acid aqueous solution or a hydrochloric acid aqueous solution; the concentration of the acid solution is 3M-12M.

8. The method for preparing the alkyne-modified acylhydrazone covalent organic framework material according to claim 4, characterized in that: The reaction temperature range of the heating in the oil bath pot is 100-150°C; the reaction temperature is preferably 100-120°C; the reaction time of the heating in the oil bath pot is 12-144h; the reaction time is preferably 36-48h.

9. The method for preparing the alkyne-modified acylhydrazone covalent organic framework material according to claim 4, characterized in that: The type of solvent selected during the extraction is one of acetone, ethyl acetate, dichloromethane, methanol, ethanol, 1,4-dioxane and tetrahydrofuran; the solvent selected during the extraction is preferably tetrahydrofuran and acetone; the extraction time is 12-72h; the extraction time is preferably 48h.

10. A proton conductor for a fuel cell, characterized in that: The invention comprises the alkyne-modified acylhydrazone covalent organic framework material as described in any one of claims 1 to 3, or the alkyne-modified acylhydrazone covalent organic framework material prepared by the method as described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Chiral separation membrane based on covalent organic framework material as well as preparation and application of chiral separation membrane

    CN111318187A

  • Covalent organic framework and methods of fabrication and uses thereof

    CN114008017A

  • Green solid-phase synthesis method of covalent organic framework material

    CN114773556A

  • Covalent organic framework material immobilized biocatalyst as well as preparation method and application thereof

    CN118064421A

  • Method for the preparation of microporous organic membranes, microporous organic membranes and use of same

    EP2992947A1

Cited By

  • Acylhydrazone-based covalent organic framework material as well as preparation method and application thereof

    CN120005135A

  • An acylhydrazone-based covalent organic framework material, its preparation method and application

    CN120005135B